2020
DOI: 10.1016/j.heliyon.2020.e03945
|View full text |Cite
|
Sign up to set email alerts
|

Impact of introducing endovascular treatment on acute ischemic stroke outcomes: A shift from an era of medical management to thrombectomy in Japan

Abstract: Background: Endovascular treatment (EVT) has increasingly become the standard treatment of acute cerebral large vessel occlusion (LVO). We evaluated the impact of introducing EVT on LVO therapy in a single center where intravenous thrombolysis (IVT) had been the only recanalization therapy. Materials and methods: Between April 2013 and March 2017, 354 consecutive patients with LVO admitted to our institution were analyzed. We compared outcomes between two chronological groups before (Pre-EVT group) and after (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Among those 13 cases with intracranial dissection, ICA was involved in only 3 cases with terminal ICA dissection. In our experience of approximately 280 mechanical thrombectomy procedures over the past 6 years, intracranial ICA dissection was identified in only this single case (0.4%) [11] , [12] , [13] , [14] . The present case demonstrated that acute cerebral artery occlusion, although rare, can occur with a dissection more proximal to the supraclinoid lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Among those 13 cases with intracranial dissection, ICA was involved in only 3 cases with terminal ICA dissection. In our experience of approximately 280 mechanical thrombectomy procedures over the past 6 years, intracranial ICA dissection was identified in only this single case (0.4%) [11] , [12] , [13] , [14] . The present case demonstrated that acute cerebral artery occlusion, although rare, can occur with a dissection more proximal to the supraclinoid lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Among these cases, extracranial dissection was more common, whereas intracranial vessel dissection was precisely described in only a small number [11 , 17] . Among approximately 250 cases of mechanical thrombectomy at our institute over the past 5 years, only these 2 patients were definitively diagnosed with iatrogenic intracranial dissection (0.8%) [20] , [21] , [22] , [23] . However, there is a current concern that instances of intracranial dissection may increase because more peripheral lesions are being treated with a variety of interventions other than the simple SR technique.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients (0.8%), out of approximately 250 cases of mechanical thrombectomy over the past 5 years at our institution, were definitively diagnosed with iatrogenic intracranial dissection caused by the thrombectomy procedure [20] , [21] , [22] , [23] . In this report, we provide the details of these 2 cases of refractory iatrogenic intracranial artery dissection that occurred during mechanical thrombectomy performed with the combined use of an SR and an aspiration catheter.…”
Section: Introductionmentioning
confidence: 99%
“…Our detailed protocol for acute ischemic stroke intervention has been previously reported. [15][16][17][18][19] Based on angiography findings, ACICAO was defined as cervical internal carotid artery (ICA) occlusion due to an atherosclerotic plaque, in which blood flow to the distal artery was completely stopped. Our main EVT indications for tandem ACICAO were as follows: (1) <8 hours from symptom onset or <24 hours from the time the patient was last seen to be well in cases where the time of symptom onset was unknown; (2) presence of intracranial LVO; (3) lack of sufficient collateral blood flow; (4) mismatch between neurological symptoms on admission and findings on imaging; (5) a score of ≥6 on the Alberta Stroke Program Early Computed Tomography Score (ASPECTS) or ASPECTS-diffusion weighted imaging.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Endovascular procedures for LVO at our institute have been previously reported. [15][16][17][18][19] The concept of our treatment strategy for tandem ACICAO is shown in Figure 1. Earlier in this cohort, percutaneous transluminal angioplasty (PTA) and carotid artery stenting (CAS) were performed before treating the intracranial lesion (CAS first-antegrade approach), while, towards the end, only PTA was performed before intracranial lesion treatment (PTA first-antegrade approach without emergent CAS).…”
Section: Evt Proceduresmentioning
confidence: 99%